Letting the Light In: A Collaborative Self-Study of Practicum Mentoring. Issue 2 (4th May 2022) - Sivia, Awneet; MacMath, Sheryl; Britton, Vandy
ABSTRACT: This article documents a year-long collaborative self-study of three teacher educators engaged in a practicum innovation in a teacher education program. This study, which is part of a larger study examining practicum-based seminars called Particulars of Practice (POP), focuses on exploring our own practices and identities within this innovation. Given this new structure in the program, we had many questions about how we each engaged with mentoring within this innovation, and what conceptions and assumptions were being surfaced for us about our roles, identities, and practices in practicum mentoring. The data included an email thread, personal reflections, and collaborative meeting transcripts that represented our experiences with the POP innovation. Using braiding as a methodological approach to honour all three sets of data, we were able to generate results that fell into two categories: reflections on the nature of self study and the knowledge gained about our identities, practices and roles from this research. We assert that the nature of self study involves vulnerability, difficult conversations, and multiplicity of perspectives. The knowledge gained from our collaborative self-study is identified as challenging preconceptions, seeing teacher candidates in new ways, and learning as a mirroring process.